Learning styles and critical thinking relationship in baccalaureate nursing education: a systematic review - Andreou, Christos; Papastavrou, Evridiki; Merkouris, Anastasios (My University, 2014)
Summary Background Critical thinking is a desirable competency for contemporary nurses although there are growing concerns supporting a disturbing paucity in its achievement. Learning styles reflect habitual behaviors which determine distinct preferences within learning situations. Evidence suggests that critical thinking could evolve through learning processes. Variances in critical thinking achievement by nursing students might therefore be influenced by individual learning preferences. The concepts “learning styles” and “critical thinking” have been independently examined in the nursing literature. No reviews were found however exploring their association in nursing education. Objectives To identify the potential relationships between learning styles and critical thinking in baccalaureate nursing students. Design Systematic review. Data Sources Eleven electronic databases were utilized without geographical and time publishing filters. Hand-searching journals and scanning references from retrieved studies were also performed. Methods Databases were searched for descriptive correlational studies which considered the relationship between learning styles and critical thinking in baccalaureate nursing students. The authors independently progressed three stage screening. Retrieved articles were reviewed at title, abstract and full text levels according to predetermined criteria. All included studies were quality appraised using a rating tool for descriptive studies. Results Six studies were finally included. Findings were grouped under four key themes: predominant learning styles, critical thinking scoring, critical thinking evolution across academic progress and learning styles–critical thinking correlations. Learning styles' diversities, weak critical thinking and inconsistent evolution through academic progress were revealed across studies. Critical thinking differed significantly between learning styles. Conclusions Commonly accepted models in nursing education were lacking in both learning styles and critical thinking. Within studies identical learning styles were found to be positively or negatively related to critical thinking. However comparative findings across studies revealed that all learning styles might be positive determinants toward critical thinking evolution, suggesting that there is a relationship between learning styles and critical thinking. Certain links between learning styles and critical thinking were supported in given settings and given nursing student populations. Further field exploration is required.
Keywords: Learning styles; Critical thinking; Nursing education; Baccalaureate nursing students